2017
DOI: 10.1007/s11888-017-0351-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Novel Radiation Treatment Techniques on Toxicity and Clinical Outcomes in Rectal Cancer

Abstract: Purpose of review Three-dimensional conformal radiation therapy (3DCRT) has been the standard technique in the treatment of rectal cancer. The use of new radiation treatment technologies such as intensity-modulated radiation therapy (IMRT), proton therapy (PT), stereotactic body radiation therapy (SBRT) and brachytherapy (BT) has been increasing over the past 10 years. This review will highlight the advantages and drawbacks of these techniques. Recent findings IMRT, PT, SBRT and BT achieve a higher target co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Colorectal cancer (CRC) is the third most common cancer worldwide, the second leading cause of cancer deaths in 2016 in the USA and is slightly more common in men. Rectal cancer accounts for one-third of all colorectal cancers and approximately 39,220 new cases of rectal cancer with an estimated 5-year overall survival rate of 65% occur each year [1][2][3][4][5]. Nowadays, nCRT followed by surgical resection is the standard treatment, which is widely used for treatment of locally advanced (cT3, 4 and/or N+) rectal cancer (LARC) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer worldwide, the second leading cause of cancer deaths in 2016 in the USA and is slightly more common in men. Rectal cancer accounts for one-third of all colorectal cancers and approximately 39,220 new cases of rectal cancer with an estimated 5-year overall survival rate of 65% occur each year [1][2][3][4][5]. Nowadays, nCRT followed by surgical resection is the standard treatment, which is widely used for treatment of locally advanced (cT3, 4 and/or N+) rectal cancer (LARC) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For patients who received radiotherapy as definite therapy, radiotoxicities have to be taken into account ( 11 ). Our current study showed that without any radioprotective agents, especially in Phase I, radiotherapy or combinational treatment rendered 30% grade 2 or above proctitis in low-lying rectal cancer patients, and among them, 7–8% grade 3 proctitis which is in need of surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Future developments may ultimately lead to traditional photon irradiation being replaced with charged particles such as protons or carbon ions, which may have even greater biological effectiveness while maintaining a favourable toxicity profile. At the present time, further clinical studies and access to treatment facilities are required to assess the applicability of these techniques fully.…”
Section: Alternatives To Standard Radiotherapy Strategiesmentioning
confidence: 99%
“…effectiveness while maintaining a favourable toxicity profile. At the present time, further clinical studies and access to treatment facilities are required to assess the applicability of these techniques fully 119,120 .…”
Section: Zerumbonementioning
confidence: 99%